KESULITAN BELAJAR OPERASI HITUNG PEMBAGIAN PADA SISWA KELAS IV SDN 84 PEKANBARU - Rika Amelia; Dea Mustika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the learning difficulties in arithmetic operations of division for the fourth-grade students of SDN 84 Pekanbaru and finds out the solutions to overcome the difficulties in arithmetic operations of division for the fourth-grade students. The research method used was a descriptive qualitative research design. The source of data obtained in the research came from five fourth-grade students. The data collection techniques used were observation, interviews, and documentation. Based on the research, there were validity tests and triangulation data. The data were analyzed through data reduction, data presentation, and conclusion. The research was conducted at SDN 84 Pekanbaru. The results of the research conducted by the researchers showed that there were some students who did not understand enough the concept of division as repeated subtraction, students who did not master enough the arithmetical operation skills of downward division, and the difficulty of the arithmetic operation of division understanding about the story.